"COVID toes": A meta‐analysis of case and observational studies on clinical, histopathological, and laboratory findings. Issue 5 (13th September 2021) - Rocha, Kelvin Oliveira; Zanuncio, Virgínia Vinha; Freitas, Brunnella Alcântara Chagas de; Lima, Luciana Moreira
Abstract: Background: Coronavirus disease (COVID‐19) is related to several extrapulmonary disorders; however, little is known about the clinical, laboratory, and histopathological characteristics of pernio‐like skin lesions associated with COVID‐19 infection. Objective: To evaluate and summarize the clinical, laboratory, and histopathological characteristics of pernio‐like lesions reported in the literature. Methods: We conducted a search of the PubMed, SciELO, and ScienceDirect databases for articles published between January 1, 2020 and November 30, 2020, following the PRISMA recommendations (PROSPERO registration ID: CRD42020225055). The target population was individuals with suspected or laboratory‐confirmed COVID‐19 with pernio‐like lesions. Observational studies, research letters, and case/series reports were all eligible for inclusion. Observational studies were evaluated using a random‐effects model to calculate the weighted mean prevalence, overall mean, and 95% confidence interval. We evaluated case studies using the chi‐square test for dichotomous variables and the Mann‐Whitney test for continuous variables. Results: A total of 187 patients from case reports and 715 patients from 18 observational studies were included. The mean age of patients was 16.6 years (range 14.5‐18.8). Feet were affected in 91.4% (87.0‐94.4%) of patients in observational studies. The proportion of patients with a positive RT‐PCR test was less than 15%. Lesion topography and morphology were associated with age. Conclusion: Lesions mostly occurred in pediatric patients, and the morphological characteristics tended to differ between pediatric and non‐pediatric populations. There is a possible multifactorial component in lesion pathophysiology. The non‐positivity of laboratory tests does not exclude an association with COVID‐19. Pernio‐like lesions may be a late manifestation of COVID‐19.